2013
DOI: 10.1586/14789450.2013.858020
|View full text |Cite
|
Sign up to set email alerts
|

Redox proteomics gives insights into the role of oxidative stress in alkaptonuria

Abstract: Alkaptonuria (AKU) is an ultra-rare metabolic disorder of the catabolic pathway of tyrosine and phenylalanine that has been poorly characterized at molecular level. As a genetic disease, AKU is present at birth, but its most severe manifestations are delayed due to the deposition of a dark-brown pigment (ochronosis) in connective tissues. The reasons for such a delayed manifestation have not been clarified yet, though several lines of evidence suggest that the metabolite accumulated in AKU sufferers (homogenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 120 publications
(175 reference statements)
1
19
0
Order By: Relevance
“…The presence of HGA in AKU tissues has been shown to increase oxidative stress on cells [25][26][27]59]; this involvement of changes in the antioxidant defences is also seen in OA with both IL-1β and IL-6 shown to dysregulate antioxidant defences in chondrocytes [60]. The significance of the IL-6 results presented in this study, showing a significant increase in pigmentation compared to HGA and IL-6 alone presented in this study, are supported by clinical evidence that there is a significant increase in serum IL-6 in AKU patients compared to control [61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of HGA in AKU tissues has been shown to increase oxidative stress on cells [25][26][27]59]; this involvement of changes in the antioxidant defences is also seen in OA with both IL-1β and IL-6 shown to dysregulate antioxidant defences in chondrocytes [60]. The significance of the IL-6 results presented in this study, showing a significant increase in pigmentation compared to HGA and IL-6 alone presented in this study, are supported by clinical evidence that there is a significant increase in serum IL-6 in AKU patients compared to control [61].…”
Section: Discussionmentioning
confidence: 99%
“…One factor that has been shown to be increased as far as ochronosis is concerned is the oxidative stress encountered by cells in AKU patient tissues [25][26][27][28]. However, the presence of HGA alone cannot be the sole factor in causing the pigmentation given that HGA is present systemically, if not from birth, hours or days shortly after for many years prior to joint manifestations caused by ochronosis.…”
Section: Introductionmentioning
confidence: 99%
“…The local expression of HGD in human osteoarticular system dramatically increases the effects in AKU cartilage degeneration. We also reported that plasma from AKU patients and an AKU human plasma model contains inflammatory cytokines, free radicals and oxidants acting as cytotoxic agents for chondrocytes (Tinti et al, 2011a;Braconi et al, 2012;Laschi et al, 2012;Braconi et al, 2013;Spreafico et al, 2013;.…”
mentioning
confidence: 99%
“…Moreover, ultra‐structural observations were complemented with biochemical and proteomic characterization of chondrocytes isolated from the ochronotic cartilage of AKU patients, indicating that AKU chondrocytes are characterized by HGA‐induced apoptosis, protein aggregation, nitric oxide release, and oxidative stress (Tinti et al, 2011a; Laschi et al, 2012; Millucci et al, 2012; Braconi et al, 2013; Spreafico et al, 2013). AKU patients have high levels of plasma serum amyloid A and pro‐inflammatory cytokines (Tinti et al, 2011b; Laschi et al, 2012; Millucci et al, 2012; Braconi et al, 2013; Millucci et al, 2014). The local expression of HGD in human osteoarticular system (Laschi et al, 2012) dramatically increases the effects in AKU cartilage degeneration.…”
mentioning
confidence: 99%
See 1 more Smart Citation